Lowering the osteotomized level of fibular osteotomy reduces neuromuscular complications while maintaining clinical efficacy in treating medial compartment knee osteoarthritis: a retrospective comparative cohort study - Ting-Yu Chang; Chih-Wei Chang; Yen-Nien Chen; Chyun-Yu Yang; Jou-Hua Wang (European Journal of Medical Research)
Abstract Background Partial fibular osteotomy (PFO) offers a minimally invasive strategy for treating medial compartment knee osteoarthritis (MKOA), yet its proximity to the peroneal nerve raises concern for postoperative neuropathy. This study investigated whether lowering the osteotomy site from the upper third to the mid-third of the fibula reduces nerve complications without compromising clinical efficacy. Methods We retrospectively reviewed 77 consecutive patients who underwent unilateral PFO from March to December 2018. After excluding 20 patients due to prior limb surgeries, or neurological comorbidities, inadequate follow-up or incomplete records, 57 patients (61 knees) with Kellgren–Lawrence grade II–III MKOA were included. Patients were allocated chronologically, with the surgical protocol modified in August 2018 after observing high neuropathy rates in the initial cohort. The osteotomy level was adjusted from 6–10 cm (upper group) to 12–15 cm (lower group) below the fibular head following early observed neuropathies. Outcomes included Oxford Knee Score (OKS), Visual Analog Scale (VAS) for pain, femorotibial angle (FTA), medial joint space ratio (MJSR), and peroneal neuropathy incidence. Radiographs were taken at baseline and 6-month follow-up. Between-group comparisons used independent t tests and Mann–Whitney U tests for continuous variables, and chi-square tests for categorical outcomes. Although a priori power analysis was performed—a limitation of this retrospective design—post hoc calculations confirmed adequate effect size detection. Mean follow-up was 13.4 months (range 12–15). Results Demographics were similar between groups (e.g., mean age 64.0 vs. 62.6 years, p = 0.67). OKS improved from 23.2 ± 5.2 to 37.7 ± 3.3 in the upper group and from 27.0 ± 8.9 to 38.1 ± 6.0 in the lower group. Over 85% of patients achieved a ≥ five-point OKS improvement, a threshold representing a clinically meaningful difference. VAS scores decreased to 1.8 ± 0.8 and 1.9 ± 0.8, respectively (p < 0.001) Peroneal neuropathy occurred in 37.9% (toe weakness) and 31.0% (numbness) of upper-group knees, with no deficits observed in the lower group (p < 0.05). Radiographic alignment and joint space changes were minimal across both cohorts. Conclusions Lowering the osteotomy to the mid-third of the fibula significantly reduced peroneal nerve injury while preserving functional improvement. These findings support mid-level PFO as a safer, technically accessible modification for MKOA treatment.